Synthesis of Syngas into Dimethyl Ether Using Cu-Zn-Al/-Alumina Bifunctional Catalyst as an Environmentally Friendly Fuel for Substituting Liquified Petroleum Gas - Suratno Lourentius (Equilibrium Journal of Chemical Engineering, 2021)
Abstract. In order to meet the need for Liquified Petroleum Gas in Indonesia, which is currently around seventy percent of which is still imported, it is necessary to find a replacement. One of the efforts to replace the Liquified Petroleum Gas is by utilizing dimethyl ether which can be produced from coal as raw material. Coal can be catalytically converted to syngas and then syngas can be catalytically converted to dimethyl ether via a direct two-step or one-step route. This paper will discuss the one-step synthesis of dimethyl ether from syngas using Cu-Zn-Al/g-Alumina as a bifunctional catalyst. The syngas used consists of carbon monoxide and hydrogen with a mole ratio of 1:2. The conversion reaction was carried out in a fixed-bed reactor at the pressure of 40 bar, the temperature of 240-300 0C, and the space velocity of 29.3-32.7 mL/g catalyst/minute. The highest conversion of CO that can be achieved is 90.08 % at a temperature of 300 oC and the space velocity of 29.3 mL/g catalyst/minute. The synthesis product was analyzed using GC. The dimethyl ether is an environmentally friendly fuel and non-toxic compound that does not destroy ozone, does not contain sulfur, and has a calorific value of about 30.5 MJ/kg which is lower than 50.56 MJ/kg